(untitled) (Research, Society and Development, 2022)
Com the excellent growth rate of the elderly, bedridden and domiciled population, highlighting the developing countries. Unfortunately, professionals are discouraged, due to the significant challenges existing in this activity area, from limitations to metabolic and physical particularities. In addition, the availability of wrong information offers the patient a low perception of the importance of oral health. Therefore, this work aims to emphasize the relevance of home care experience in the community during graduation, starting from the anamnesis until the clinical care in the space where the patient resides. To support this work’s discussion, the researchers searched articles in the databases such as Scielo, Bv Salud, Pubmed, and journals in conditions of national and international sources, with descriptors such as dental home care, elderly and multidisciplinary team. As a result, the selected contents show the importance of the subject of interest. Furthermore, the article shows the relevance of aggregation of home care subjects to the dentistry curriculum grid in theory and practice.